Problems of Diagnosis and Management of a Patient with Suspected Scurvy: A Case Report - Gunadi, Hendra; Gotera, Wira (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Vitamin C is a substance needed by the human body to maintain metabolic function. Scurvy is a disease caused by vitamin C deficiency. This disease is often forgotten in the era of modern medicine. Vitamin C (ascorbic acid) plays a role in the formation of type IV collagen. Type IV collagen is an essential component of the walls of blood vessels, skin, and the basement membrane zone that separates the epidermis from the dermis. Three things must be met to diagnose scabies, namely a history of insufficient vitamin C intake, the presence of clinical manifestations typical of scabies, and biochemical indices, namely low levels of vitamin C in the blood (serum, white blood cells, and whole blood) and low urinary excretion levels. In patients with scabies who already have clinical manifestations, immediate vitamin C replacement is needed. A case of a male patient with suspected scabies with various clinical manifestations has been reported who improved with direct vitamin C replacement therapy. Early diagnosis and appropriate treatment can improve the prognosis in patients with scabies.